2023
DOI: 10.3389/fendo.2023.1156583
|View full text |Cite
|
Sign up to set email alerts
|

From mitochondria to sarcopenia: role of 17β-estradiol and testosterone

Abstract: Sarcopenia, characterized by a loss of muscle mass and strength with aging, is prevalent in older adults. Although the exact mechanisms underlying sarcopenia are not fully understood, evidence suggests that the loss of mitochondrial integrity in skeletal myocytes has emerged as a pivotal contributor to the complex etiology of sarcopenia. Mitochondria are the primary source of ATP production and are also involved in generating reactive oxygen species (ROS), regulating ion signals, and initiating apoptosis signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 160 publications
0
7
0
Order By: Relevance
“…Age-related testosterone decline is associated with the development of sarcopenia ( 32 , 33 ) and, testosterone replacement therapy has been reported to increase muscle strength and lean body mass ( 34 , 35 ). In addition, randomized controlled trials in patients with liver cirrhosis have demonstrated the benefit of testosterone administration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related testosterone decline is associated with the development of sarcopenia ( 32 , 33 ) and, testosterone replacement therapy has been reported to increase muscle strength and lean body mass ( 34 , 35 ). In addition, randomized controlled trials in patients with liver cirrhosis have demonstrated the benefit of testosterone administration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced muscle function is linked to mitochondrial dysfunction ( 38 , 39 ). Mitochondria are critical organelles in skeletal muscle responsible for regulating its metabolic status, including chemical energy (ATP) production, regulation of intracellular Ca 2+ homeostasis, modulation of cell proliferation, and integration of apoptotic signaling ( 40 , 41 ). In the present study, the loss of Ovarian E 2 resulted in diminished ATP production, and WBVT treatment rescued this decline, similar to E 2 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic balance of cellular mitochondrial content is maintained through the opposing processes of mitochondrial biogenesis and mitophagy ( 41 ). The main mitophagy pathway that has been investigated in the context of exercise involves PINK1 and Parkin ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during our correction for confounding factors in the interaction test for lumbar spine bone density and sarcopenia, we also found a more significant effect of gender on the negative association between lumbar spine bone density and sarcopenia. This may be related to the fact that estrogens, androgens, and testosterone are all associated with the metabolism of skeletal and muscular tissues in humans [ 19 ]. Estrogens maintain skeletal muscle contractility and prevent OP [ 20 ], while androgens and testosterone promote myoblast proliferation [ 21 ].…”
Section: Discussionmentioning
confidence: 99%